Magnetooptical response of permalloy multilayer structures on different substrate in the IR–VIS–UV spectral range. (13th September 2019) - Patra, Rajkumar; Mattheis, Roland; Stöcker, Hartmut; Monecke, Manuel; Salvan, Georgeta; Schäfer, Rudolf; Schmidt, Oliver G; Schmidt, Heidemarie
Abstract: The magnetooptical (MO) response of Ru/Py/Ta thin film stacks with 4, 8, and 17 nm thick Ni81 Fe19 permalloy (Py) films on a SiO2 /Si and a ZnO substrate was measured by vector magnetooptical generalized ellipsometry. The MO response from VMOGE was modelled using a 4 × 4 Mueller matrix algorithm. The wavelength-dependent, substrate-independent and thickness-independent complex MO coupling constant ( Q ) of Py in the Ru/Py/Ta thin film stacks was extracted by fitting Mueller matrix difference spectra in the spectral range from 300 nm to 1000 nm. Although the composition-dependent saturation magnetization of Ni x Fe1− x alloys ( x = 0.0…1.0), e.g. of Ni81 Fe19, is predictable from the two saturation magnetization end points, the MO coupling constant of Ni x Fe1− x is not predictable from the two Q end points. However, in a small alloy range (0.0 < x < 0.2 and 0.8 < x < 1.0) the composition-dependent Q of Ni x Fe1− x can be interpolated from a sufficiently high number of analyzed Ni x Fe1− x alloys. The available complex MO coupling constants of six different Ni x Fe1− x ( x = 1.0 to 0.0) alloys were used to interpolate MO response of binary Ni x Fe1− x alloys in the range from x = 0.0 to x = 1.0.